Region and Rabies: A Review of Geographical Variations, Challenges and Strategies for Control - Bharti Koria (GAIMS Journal of Medical Sciences)
Rabies, one of the oldest known zoonotic diseases, continues to claim thousands of lives every year—despite being entirely preventable. It disproportionately affects populations in Asia and Africa, particularly in low-resource rural regions where dog-mediated transmission remains endemic. This review explores the interplay between regional contexts and rabies epidemiology, highlighting disparities in disease burden, surveillance capacity, vaccine access, health infrastructure, and cultural beliefs. It also outlines successful regional interventions, emphasizing the need for geographically tailored strategies. With the global “Zero by 30” goal in sight, addressing these regional dynamics is key to achieving equitable and sustainable rabies elimination.